Detection of Factor XI Deficiency (FXID) and Complex Vertebral Malformation (CVM) in Bali Cattle - Sri Wahyuni Siswanti; Cece Sumantri; Jakaria jakaria (Media Peternakan, 2014)
Factor XI Deficiency (FXID) is caused by imperfect insertion of poly adenine which is resulted in introduction of premature stop codon in FXI gene.  Substitution of guanine into thymine in SLC35A3 gene caused Complex Vertebral Malformation (CVM). The research was aimed to detect the presence or absence of a genetic defect mainly CVM using SLC35A3 gene and FXID using FXI gene in Indonesian Bali cattle. The presence of this genetic defect may have a significant economic impact on the breeding program. The research of genetic defect was done mostly in dairy cattle, but there was no report for screening of genetic defect in Bali cattle. In this study, 303 fresh blood samples and 22 semen samples which were collected from Indonesian Bali cattle breeding center (BPTU HMT Denpasar, BPT HMT Serading West Nusa Tenggara and district Barru South Sulawesi) and artificial insemination centre (BBIB Singosari and BIBD Baturiti) were used for screening of FXID and CVM. The amplicons of FXI gene were obtained by using PCR and that for SLC35A3 gene were obtained by using PCR-RFLP method with PstI restriction enzyme. These PCR products were analyzed by using 2% agarose gels electrophoresis. All genotypes were confirmed by DNA sequencing to determine an allele mutant. The allele mutant was not found in all of the samples. The result of this study showed that CVM and FXID were not detected in Bali cattle from Indonesian Bali cattle breeding and artificial insemination centres.Key words: Bali cattle, genetic defect, SLC35S3 gene, factor XI gene